Obtaining Clean and Well-dispersed Pt NPs with a Microwave-assisted Method - Armendáriz, Víctor Rolando R. (2014)
Carbon-supported platinum nanoparticles Pt/C (NPs) are used in many fields of science. These kinds of materials have been extensively studied in electrochemistry due to the fact that they are applied in fuel cell technology. Although there are a myriad of methods for Pt NP synthesis, the need for obtaining Pt/C NPs with a good dispersion (covering over the entire support), a narrow size distribution, and clean surface (among other parameters) is far to be overcome. On this sense herein we describe a very easy and quick method of synthesis of highly dispersed Pt NPs followed by a simple electrochemical cleaning step. The catalysts were electrochemically characterized by studying their behavior in 0.5 M H2SO4 and also by using CO as a probe during the CO electro-oxidation reaction (COEOR). This paper shows how to obtain highly dispersed and clean Pt/C NPs that produce very reproducible results. Besides, we demonstrate how the presence of impurities negatively affects the electrochemical reproducibility of Pt NPs with a clear impact on their catalytic activity.